Policy Scenarios in Ethiopian Higher Education Expansion: Challenges of Program Diversification and Its Future Implications - Teklu Tafase Olkaba; Wakgari Tasisa Duressa (University of Sofia, 2020)
The study investigated the extent of Ethiopian higher education expansion policies and its program diversification responding to the local market demands and realities on the ground. The study explored a range of literature on Ethiopian higher education policy scenarios within national development policies. The study was guided by one research question: To what extent the expansion policy and program diversifications in Ethiopia higher education responded to the demands and realities of the local economy? The literature review, document survey, and focus group discussions were used to examine the expansion policies and its program diversification processes. The finding of the study illustrates that the responsiveness of Ethiopia higher education expansion policy brought a tremendous increase in enrollments within a short period of time. Moreover, the finding confirms that the graduate mix policy resulted poor program relevance and graduate unemployment crisis. Based on the find-ings of the study, conclusions were made for policy makers to critical revisit the policy scenarios in Ethiopian higher education expansion, diversification and relevance in line with national, regional and global manpower demand.